2016
DOI: 10.1016/j.siny.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Cervical etiology of spontaneous preterm birth

Abstract: SUMMARY The cervix functions as a barrier between the uterus and vagina and keeps the uterus closed until term so that the fetus can develop. For delivery the cervix must soften and dilate, and finally reconstitute to close the uterus. This complex process involves precisely timed activation of molecular and microstructural events. Spontaneous preterm birth (sPTB) can result from aberrant timing of these events in the cervix. Unfortunately, the pathophysiology of sPTB due to cervical causes remains unclear and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 50 publications
(63 reference statements)
0
80
1
6
Order By: Relevance
“…To accommodate this drastic dilation of the cervix at time of delivery, the extracellular matrix (ECM) of the tissue must drastically remodel, reorganize, and soften during gestation. The timing and characteristics of this remodeling behavior is currently an active research focus because it is hypothesized that premature remodeling in pregnancy can lead to a preterm birth [2], a leading cause of neonatal death or significant neonatal morbidity [3]. In an effort to characterize the remodeling behavior of human cervical tissue, the objective of this study is to measure and quantify the collagen fiber orientation and dispersion (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To accommodate this drastic dilation of the cervix at time of delivery, the extracellular matrix (ECM) of the tissue must drastically remodel, reorganize, and soften during gestation. The timing and characteristics of this remodeling behavior is currently an active research focus because it is hypothesized that premature remodeling in pregnancy can lead to a preterm birth [2], a leading cause of neonatal death or significant neonatal morbidity [3]. In an effort to characterize the remodeling behavior of human cervical tissue, the objective of this study is to measure and quantify the collagen fiber orientation and dispersion (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the 1970s reported that the collagen network in the cervix is comprised of three distinct zones – one zone of collagen in the middle of the stroma that is oriented circumferentially around the endocervical canal (which provides resistance to cervical dilation) and an inner (toward the endocervical canal) and outer (towards the vagina) zone of collagen fibers that run parallel to the endocervical canal These out and inner zones of collagen likely attach the cervix to the uterus. (6,12,13; Figure 2) Recently, Yao et al used optical coherence tomography (OCT) to measure the orientation of collagen fibers and their distribution in the upper cervix using hydrated unfixed samples, and the study reported in general there are two radial zones and the outer zone contains collagen fibers that are circumferentially oriented. (14; Figure 3) Reusch et al used second harmonic generation microscopy to show that collagen fibers in the cervix form interweaving zones that change as one moves from the external to internal os.…”
Section: Normal Human Cervical Tissue Structure and Function – The Prmentioning
confidence: 99%
“…Since “cervical insufficiency” can be a confusing clinical term, recently it was proposed to adopt the term “premature cervical remodeling” as it does not rely on clinical history but focuses on the physical changes in the cervix. (6) In order to use this terminology, however, we must establish objective detection and quantification methods to diagnose premature cervical remodeling. Currently, several groups are working on developing non-invasive methods to quantify cervical remodeling and these are discussed in the second issue of this series in Seminars in Perinatology.…”
Section: Where Do We Go Now?mentioning
confidence: 99%
See 1 more Smart Citation
“…The cervix alone is very complex, with an extracellular matrix (ECM) consisting of interweaving layers: inner and possibly outer zones of collagen fibers oriented parallel to the endocervical canal (hypothesized to prevent the cervix from tearing off the uterus during dilatation), and a circumferential middle band of collagen (hypothesized to serve as a ratchet to control dilation) that seems to undergo the most dramatic change during pregnancy. 70 Relationships of proteins, cells and other factors within the cervical ECM clearly determine its biomechanical properties such as softening, shortening, and dilation. 70 Further, the internal os, as compared to the external, has greater collagen crosslink heterogeneity and a circumferential ring containing 50–60% smooth muscle that can be induced to contract ex vivo (i.e., there appears to be a functioning sphincter).…”
Section: Precision Medicine For Parturition: a Contemporary Answer Tomentioning
confidence: 99%